Effects of dietary protein level on growth and ammonia excretion of leopard coral grouper, Plectropomus leopardus (Lacepede, 1802) - Xia, S.; Sun, Z.; Feng Z. Zhang, S.; Rahman, M.M.; Rajkumar, M. (Universiti Kebangsaan Malaysia, 2015)
The effects of dietary protein level on the growth performance and ammonia excretion of the leopard coral grouper, Plectropomus leopardus were investigated for eight weeks. Fish were fed diets with 40, 45, 50, 55 and 60% crude protein levels in separate recirculating systems. Fish fed with the 50% crude protein containing diet showed the best ingestion rate, which was significantly higher than that found in the other groups. As the dietary protein level increased, the specific growth rate increased significantly and it reached the highest level at 50% crude protein containing diet. Based on the results of all measured parameters 50% protein containing diet was the best among all test diets. The regression equation for dietary protein level versus ammonia excretion indicated that the optimal dietary protein level with the least ammonia excretion was 53.14%. More research is still needed to elucidate the effects of 53.14% crude protein containing diet on the specific growth rate, feed conversion ratio, protein efficiency ratio and ingestion rate of leopard coral grouper before recommending this level. Until then, 50% protein containing diet can be recommended for leopard coral grouper culture in the recirculation system.